Clustering of oil droplets in o/w emulsions: Controlling cluster size and interaction strength. (August 2019) - Fuhrmann, Philipp L.; Sala, Guido; Stieger, Markus; Scholten, Elke
Abstract: Clustering of oil droplets changes the rheological properties of oil-in-water (o/w) emulsions and can be used as a tool to structure foods. The aim of this study was to manipulate both oil droplet cluster size and cluster strength in liquid o/w emulsions, and to investigate the effect of these parameters on the rheological properties. Clustered emulsions were prepared using three different methods: (i) clustering by protein-proanthocyanidin interactions, (ii) clustering by hetero-aggregation of oppositely-charged emulsion droplets, and (iii) enzymatic clustering of protein-stabilised droplets using transglutaminase. Clustering by protein-proanthocyanidin interactions allowed to control oil droplet cluster size from 1 to 140 μm. Clusters decreased in size upon both an increase and decrease in pH, but were stable against changes in ionic strength. Hetero-aggregation of oppositely-charged oil droplets (gelatine/whey protein and gelatine/DATEM) allowed to control cluster size from 1 to 40 μm. Clusters showed a strong decrease in size in response to changes in pH and a small decrease in size with increasing ionic strength. Enzymatic clustering did not allow to control cluster size. Cluster strength of proanthocyanidin-stabilised clusters was found to be higher than that of hetero-aggregated clusters. Stabilisation of clusters was likely induced by different protein-proanthocyanidin interactions such as H-bridges, π-π stacking, and hydrophobic interactions, whereas hetero-aggregation is based on electrostatic interactions. Upon clustering, emulsion viscosity increased by up to three orders of magnitude. We conclude that protein-proanthocyanidin interactions and hetero-aggregation are effective methods to tune droplet cluster size and strength in o/w emulsions, and that cluster size and interaction strength control the rheological properties of o/w emulsions with clustered oil droplets. Graphical abstract: Unlabelled Image Highlights: Hetero-aggregation and proanthocyanidin-based crosslinking allow droplet clustering. Cluster size and interaction strength can be controlled. The effective oil volume fraction of emulsions was increased significantly by clustering. Controlled clustering of oil droplets in o/w emulsions allows steering the emulsion viscosity.